Modellazione 3D e Archeologia dell'Architettura: l'eremo di Sant'Alberto di Asciano (SI) (Archeomatica, 2014)
The research is focused on 3D modelling applied to Archaeology of Architecture. The case study is the church of Sant'Alberto, Asciano (Siena). Both the interior and exterior were deepened using a terrestrial laser scanner and high resolution images were acquired to create a photorealistic model. This has been the basis for archaeological analysis allowing to carry out geometric measurements, to fragment the building in constructive phases, to instantly put in relation inner/external walls, and also to extrapolate CAD drawings. The data of the study and the model were imported into GIS environment for querying about material and constructive technique, and for disassembling/reassembling the monument on the basis of the constructive phases.